2014
DOI: 10.2340/00015555-1634
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Depression and Itch in Patients with Atopic Dermatitis in an Experimental Setting: A Regression Analysis

Abstract: It is known that itch is associated with psychological variables, but it is not known whether personality characteristics, depression or anxiety are predictors of experimentally induced itch in patients with atopic dermatitis (AD). In this study itch was induced in 27 patients with AD and 28 healthy controls by the presentation of an experimental video on crawling insects and skin diseases. Itch intensity was measured by self-ratings and by observing the number of scratch movements. Itch increase was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 37 publications
3
72
2
7
Order By: Relevance
“…In 2 different studies, Gupta et al (4,27) noticed a direct positive relationship between the severity of pruritus and the severity of depression in patients with psoriasis. Severe pruritus may contribute to a negative affective state, but recent studies indicate that depression may increase pruritus perception and act as a predictor of itch (29,30). Results from a pioneering experimental study showed that negative emotions can lead to higher levels of both itch and pain (29).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In 2 different studies, Gupta et al (4,27) noticed a direct positive relationship between the severity of pruritus and the severity of depression in patients with psoriasis. Severe pruritus may contribute to a negative affective state, but recent studies indicate that depression may increase pruritus perception and act as a predictor of itch (29,30). Results from a pioneering experimental study showed that negative emotions can lead to higher levels of both itch and pain (29).…”
mentioning
confidence: 97%
“…Results from a pioneering experimental study showed that negative emotions can lead to higher levels of both itch and pain (29). Thus, both depression and certain personality characteristics have been identified as predictors of experimentally induced pruritus in patients with atopic dermatitis (30). Some personality characteristics have been associated with pruritus, e.g.…”
mentioning
confidence: 98%
“…In individuals with AD, pruritus can lead to longterm psychological problems, including anxiety, depression and suicidal ideation [50][51][52][53][54]. The prevalence of mental health issues is higher in patients with AD than in the general population, and pruritus has a detrimental effect on comfort levels and sleep [52,[55][56][57].…”
mentioning
confidence: 98%
“…An extensive review by Friedman and Kern (2014) indicate that factors such as depression and anxiety, both strongly associated with trait Neuroticism, play a part in many illnesses, including eczema (Al-Ahmar & Kurban, 1976;Kim et al, 2006;Mirzara et al, 2012;Schut et al, 2014;Slattery & Fox, 2011;Takahashima et al, 2013). Depression has been thought to only be a strong association of eczema when co-morbidity with anxiety is accounted for (Klokk et al, 2010), particularly with face eczema.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently indicated that high levels of trait Neuroticism are found in eczema patients (Al-Ahmar & Kurban, 1976;Schut et al, 2014;White et al, 1990) as well as temperaments that indicate lower levels of emotional stability (Takahashi et al, 2013;White et al, 1990). Correlations with other Big Five related factors, however, have been less consistent; Extraversion has been thought to negatively associated with eczema (Schut et al, 2014), whilst other researchers indicate no correlation (Al-Ahmar & Kurban, 1976). In a clinical sample Schut and colleagues (2015) investigated the associations between personality traits Agreeableness and self-consciousness and psoriasis (a frequent skin disease accompanied by itch).…”
Section: Introductionmentioning
confidence: 99%